Expectant mothers' readiness to initiate preventive oral health care for their children - Almoudi, M.M.; Hussein, A.S.; Doss, J.G.; Schroth, R.J. (Elsevier, 2016)
Objectives: To assess the readiness and barriers faced by expectant mothers in Libya to initiate preventive oral health care for their children. Methods: A cross-sectional quantitative survey was conducted based on a structured questionnaire in a face-to-face interview. Four hundred and thirty seven expectant women who attended three main public maternal centers in three different districts in Libya were invited to participate. Descriptive statistics, bivariate and logistic regression analyses were performed. Statistical significance (p-value) was set at 0.05. Results: The response rate was 89.0% (389/437). In terms of knowledge readiness, less than half of the participants had adequate knowledge regarding healthy dietary habits, oral hygiene care, and preventive dental attendance (44.7%, 35.7% and 56.8% respectively) with fewer than one-third (27.5%) of mothers ready in terms of overall knowledge readiness. The majority demonstrated readiness in terms of their attitude toward the importance of their children's oral health (89.9%) and their willingness to initiate preventive oral health care for their children (98.7%). Only 17.7% of participants demonstrated an overall readiness to initiate preventive oral health for their children. Overall readiness significantly differed based on maternal age and number of children (p = 0.001 and p = 0.04, respectively). Most mothers (84.6%) faced barriers that prevented them from initiating preventive oral health for their children. Barriers included busy schedules at work/home (34.7%), insufficient information (29.3%), and insufficient skills (13.7%). Conclusion: These findings highlight the limited basic dental knowledge of the expectant mothers in Libya and the need to develop and implement appropriate oral health education programs for the expectant women and young mothers.